DEVELOPMENT OF AGRO-TOURISM IN DOBROGEA REGION, ROMANIA, IN THE CONTEXT OF EUROPEAN INTEGRATION - Elena SIMA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The objective of the present paper is to make an analysis of agro-tourism activity development in Dobrogea – a historical province from Romania's South-East extremity, in order to identify the main trends and changes in the period after Romania’s accession to the European Union, using official empirical data and specific indicators: agro-tourism offer in terms of number of agro-tourism boarding houses (they refer only to accommodation in standardized tourist units) and number of places/beds in use (number places-days) in this type of accommodation units; agro-tourism demand in terms of number of tourist overnight stays in the agro-tourism boarding houses; the net utilization index of the agro-tourism boarding houses capacity. The whole volume of information presented in this paper was obtained from national statistics, from governmental and non-governmental sources, as well as from articles and studies published in specialized journals. The results showed that the agro-tourism offers were among the most preferred destination, as most tourists feel safer here and agro-tourism boarding houses services are more and more attractive. However, the agro-tourism potential in Dobrogea should be much better exploited, the demand/offer ratio should be in balance, the agro-tourism boarding houses destinations should be more intensively promoted and service quality should be improved in order to increase the agro-tourism flow and attractiveness of this region.